Changes in body composition in male adolescents with childhood‐onset GH deficiency during transition. (29th May 2019) - Binder, Gerhard; Donner, Julia; Becker, Bettina; Bauer, Jana Leonie; Schweizer, Roland
Abstract: Objective: Restarting rhGH in adolescents with childhood‐onset (CO‐) GHD is usually based on GH retest, IGF‐1, additional pituitary hormone deficiencies, pituitary morphology and history. Short‐term changes in body composition in adolescents with CO‐GHD when off rhGH may contribute to the identification of those in need of treatment continuation. Design: This is a longitudinal single‐centre study. Patients and measurements: The body composition of 90 male adolescents with low‐likelihood severe GHD of adolescence was measured by DXA at the time of rhGH discontinuation and 6 months thereafter. At diagnosis, mean age was 5.4 years, height was −2.68 SDS and stimulated GH peak was 5.1 ng/mL. RhGH treatment was stopped at 16.7 years at near‐final height of −0.44 SDS. The adolescents were re‐examined after 3 months off rhGH using both IGF‐1 and GHRH‐arginine tests. Severe GHD of adolescence was defined both by stimulated GH < 16 ng/mL and by IGF‐1 < −1.90 SDS. Results: Males with severe GHD of adolescence (n = 8) gained more relative and absolute fat mass and lost significantly more relative lean body mass after 6 months off rhGH than healthy individuals (n = 82; P < 0.001). The sum of absolute fat mass gain and lean body mass loss (=body composition changes score; BCC score) correlated highly with the GH peak (R = 0.17; P < 0.001). A BCC score >7.0 kg was 88% sensitive and 94% specific for detecting severe GHD of adolescence (AUC = 0.975). Conclusions: Short‐term body composition changes when off rhGH are good clinical markers of severe GHD in male adolescents. The novel BBC score is an aggregate of these changes.